Histopathology of susceptible and resistant Capsicum annuum cultivars infected with Ralstonia solanacearum - Rahman, M. A.; Abdullah, H.; Vanhaecke, M. (Wiley, 1999)
The vascular colonisation of resistant and susceptible hot chilli (Capsicum annuum) cultivars by Ralstonia solanacearum was examined using transmission electron microscopy. Tap roots of artificially-inoculated plants, grown in sterilised soil were investigated to observe the morphological barriers involved in the restriction of bacterial spread. In the resistant cultivar, several responses induced in response to bacterial infection, were observed. First, a cell wall coating material developed together with swelling of the primary wall of the xylem vessels, limiting the bacterial spread. Second, formation of various types of vesicles in the vascular parenchyma cells, which enveloped the bacterial mass and also partly restricted the pathogen spread. Third, induction of hypersensitive reaction in the xylem vessels resulted in the distortion and lysis of the bacteria. In the susceptible cultivar, vascular coating, production of vesicle and induction of hypersensitive reaction were not observed and bacterial spread was not limited. Rapid vascular colonisation of the susceptible cultivar seemed to be generalised which resulted in the rapid wilting of affected plants. Other reactions involved in both resistant and susceptible cultivars include disorganisation of cytoplasm of parenchyma cells, disintegration of nuclei, and rupturing of xylem vessel walls. The restriction of pathogen spread associated with the resistance in C. annuum to bacterial wilt was mainly attributed to some induced, morphological and physical barriers.